Collaboration of the 'Merah Putih' Village Cooperative Business Model and Public Kitchens in Supporting Local Food Security - Sukaris, Sukaris; Wardana, Havy; Cholifah, Anik Nur; Indarto, Tomi; Suwandi, Suwandi; Wati, Hernum Daya; Suwarno, Suwarno; Widiyawati, Wiwik; Mulyani, Endah (International Journal of Management Science and Information Technology, 2026)
Local food security is a strategic issue in sustainable development, especially amidst challenges in food distribution, unequal access, and increasing nutritional needs of the community. Strengthening community-based food systems has encouraged the emergence of the Merah Putih Village Cooperative (KDMP) as a village economic aggregator and the Free Nutritional Meal Program (MBG) through public kitchens as food providers for vulnerable groups. The collaboration between these two institutions is seen as capable of shortening the supply chain, increasing the absorption of local products, and strengthening the people's economy. Data were collected through in-depth interviews, observations, documentation studies, and focus group discussions, then analyzed using thematic analysis techniques to obtain a comprehensive contextual understanding. The research findings indicate that collaboration between KDMP and public kitchens has significant potential to build a more organized food distribution chain, provide a stable market for village products, and create economic opportunities for local communities. However, institutional fragmentation, technological limitations, varying procurement mechanisms, and the lack of quality standards remain key obstacles. This study concludes that collaborative business models can be an effective strategy for building an inclusive and resilient local food ecosystem if supported by strengthened governance, supply chain digitalization, and cross-sector partnerships. Theoretically, this research contributes to the development of collaborative governance and community-based business models by demonstrating that synergy between local organizations can increase food system resilience while expanding the role of cooperatives as community economic institutions. Consequently, local governments and program managers need to promote collaborative regulation, institutional capacity building, and investment in logistics infrastructure to ensure the sustainability of village-based food systems.